Micro/nanostructured hyaluronic acid matrices with tuned swelling and drug release properties - Minaberry, Yanina Susana (2013)
Hyaluronic acid (HA) hydrogels were structured in the form of porous monoliths by means of the ice-segregation-induced self-assembly (ISISA) method coupled with freeze-drying. Physical and chemical parameters were explored in order to fine-tune the microstructure and the incidence on both swelling and dissolution behavior in aqueous media. Gentamicin-loaded HA matrices with tuned drug release properties were also prepared; their inherent properties and behavior in solution are discussed in the framework of thermal analysis and scanning electron microscopy inspection.